Occupational stress and UN peacekeepers. (17th October 2014) - Tobin, J.
Abstract : Background: Ireland has been actively involved in peacekeeping operations since the 1950s. The unique psychological stressors associated with this form of military activity have been under-recognised and under-researched. Aim: The aim of this paper is to bring to the attention of mental health professionals, who have been caring for military and retired military peacekeeping personnel, the unique difficulties associated with peacekeeping and how they can impact upon the mental health of the peacekeeper. Methods: The nature of peacekeeping is outlined. There is a short review of the limited literature on the mental health effects of this kind of military deployment. There is also an outline of the positive outcomes for the majority of those who have served as peacekeepers. Results: Both the negative and the positive mental health outcomes depend on the particular mission. Each mission is different and the nature of a mission also changes over time. Post-traumatic stress disorder rates can vary from 3% to 15% of a peacekeeping cohort, depending upon the nature of the violence associated with the mission. The vast majority of peacekeepers have found their peacekeeping deployments as an enriching experience. Conclusion: Peacekeepers are often witnesses as well as the victims of traumatic events. The restrictions placed upon their military role by the mission mandate can be a source of stress for them. Their mental health needs to be supported during the mission and after they have returned home.